Review of surface measurement methods towards nondestructive internal surface assessment - Kwan Zhi Teh; Saikat Medya; Sugandhana Shanmuganathan; Swee Hock Yeo (Advanced Manufacturing)
Metal additive manufacturing techniques have enabled the ability to construct complex internal channels, but they create rough surfaces of varying qualities. Surface texture is vital to engineering analysis and is usually emblematic of product quality. The problem, however, lies with the difficulty in measuring or assessing such internal surfaces. As they are concealed by nature, it is difficult to measure them non-destructively through conventional measurement methods. Non-destructive means are favored as they save materials and time, but a proper review of less-known available methods is first required to reveal and understand the proper means of evaluating internal surface non-destructively. This paper reviews the measurement methods of capacitance, vibration analysis, optical techniques, X-ray computed tomography, and replica methods critically with their working principles, pros and cons discussed. Their current applications in literature are evaluated to understand the appropriateness for internal surface applications. Endoscopic non-destructive testing (NDT), X-ray computed tomography, and replica methods are found to be rather suitable. Propositions are also given for enabling the less suitable methods. Amongst all these techniques, X-ray computed tomography stands out as a great method for such purposes and would appear to be the best path forward for development, provided that its resolution issues are improved through better reconstruction algorithms, novel scanning methodologies, or improved X-ray energy sources.